Educational technologies as tools: Critical considerations on a fundamental metaphor - Giselle Martins dos Santos Ferreira; Márcio Silveira Lemgruber (Arizona State University, 2018)
In the current National Education Plan (2014-2024), the word technology appears repeatedly in the description of strategies proposed to support the goals defined in the document. Although the term tool is not explicitly included in the text, the idea of technology as tool is widely disseminated in academic and marketing discourses on educational technology. This image can be viewed as a fundamental (Perelman Tyteca-Olbrecht) or conceptual (Lakoff Johnson) metaphor, that is, a metaphor that encapsulates certain ways of perceiving, thinking and relating to the world, and, thus, structures thought and action. This article discusses the metaphor of technology as tool as an insidious and doubly dangerous conception since, whilst it supports a view of technology as neutral, expressed in a perspective on the impacts of certain artefacts as depending only on their uses, the metaphor reflects a reductionist perspective on the relationship between human and technical. The text discusses the ways in which this metaphor supports conceptions of technology that need to be examined, as the simplistic and uncritical view it promotes tends to obscure fundamental questions regarding the multiple contexts of production and consumption of artefacts created by an industry with agendas and interests that are primarily commercial.